ANALISIS POTENSI PETANI KOPI SEBAGAI UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT DALAM PERSPEKTIF EKONOMI ISLAM - Jiter, Arda; Fasa, Muhammad Iqbal; Suharto, Suharto (STAI Darul Qalam Tangerang, 2025)
Ulubelu District is one of the coffee production centers in Tanggamus Regency, especially in Pekon Gunung Tiga. Pekon Gunung Tiga is located in the area of Ulubelu District, Tanggamus Regency, Lampung Province. Based on (Regulation of the Minister of Agriculture, 2014) coffee is a plantation commodity that plays an important role in the Indonesian economy. Coffee is basically a plant that is very easy to find in various regions in Indonesia. This plant is generally grown in mountains that have cold air temperatures. Abundant natural resources should be looked at in depth so that their use can be very optimal, one of the natural resources that has extraordinary potential is coffee, coffee is one of the plantation commodities that is quite developed in Indonesia, The problem that arises is that many people after harvesting coffee do not have any side jobs anymore so that it leads to famine. The method in this study is qualitative by relying on primary data in the form of interviews and secondary. The results that researchers found are that the coffee harvest is not as large as a whole to meet the needs of one year, but also depending on the weather, if it is good, the harvest is also large and vice versa.